Persepsi mahasiswa sebagai pemilih pemula terhadap normalisasi politik uang dalam pemilihan umum (Komisi Pemberantasan Korupsi, 2023)
The practice of money politics by some parties has been considered normal in elections in Indonesia. Money politics has been extensively discussed in the literature regarding voter behaviour in Indonesia from a political, sociological, psychological, and rational choice (political economy) perspective. Some studies focus on the influence of money politics in elections. Several international studies have also discussed academic explanations regarding the electoral impact of money politics. Beginner voters are a segment of voters who are considered more rational and not as pragmatic, with an increased awareness of the importance of holding elections with integrity. This study aims to determine students' perceptions as first-time voters of the normalization of money politics in elections. This research uses qualitative methods with a descriptive approach. The data used in this study is primary data in the form of structured interviews using questionnaires and secondary data. The research results show that most respondents know the prevalence and forms/types of money politics. Respondents have a perception that tends to be balanced regarding whether they agree or disagree that money politics is a common practice in elections in Indonesia. Factors that influence respondents' perceptions include elements in the respondent's self, factors on targets or objects, and situation/context factors.